Plant growth promoting bacteria in Brachiaria brizantha - Pinheiro Silva, Mylenne Calciolari [UNESP]; Figueiredo, Aline Fernandes [UNESP]; Andreote, Fernando Dini [UNESP]; Bran Nogueira Cardoso, Elke Jurandy [UNESP] (Springer, 2013)
Brachiaria brizantha is considered one of the preferred fodders among farmers for having high forage yield and large production of root mass. The association of beneficial bacteria with these grasses can be very valuable in the recovery of the pasture areas with nutritional deficiency. With the aim of studying this possibility, we carried out the sampling of soil and roots of B. brizantha in three areas (Nova Odessa-SP, So Carlos-SP and Campo Verde-MT, Brazil). Seventy-two bacterial strains were isolated and used in tests to evaluate their biotechnological potential. Almost all isolates presented at least one positive feature. Sixty-eight isolates produced analogues of indole-3-acetic acid, ten showed nitrogenase activity when subjected to the method of increasing the concentration of total nitrogen (total N) in the culture medium and sixty-five isolates showed nitrogenase activity when subjected to acetylene reduction technique. The partial sequencing of 16S rRNA of these isolates allowed the identification of seven main groups, with the prevalence of those affiliated to the genus Stenotrophomonas (69 %). At the end, this work elected the strains C4 (Pseudomonadaceae) and C7 (Rhodospirillaceae) as promising organisms for the development of inoculants due to their higher nitrogenase activity.
Keywords: Diazotrophic; Brachiaria brizantha; Nitrogen; Nitrogenase; Indole-3-acetic acid; 16S rRNA